High dose radiation with chemotherapy followed by salvage esophagectomy among patients with locally advanced esophageal squamous cell carcinoma. Issue 3 (21st March 2017) - Lertbutsayanukul, Chawalit; Tharavej, Chadin; Klaikeaw, Naruemon; Prayongrat, Anussara; Lowanitchai, Chutinan; Sriuranpong, Virote
Abstract : Background: Locoregional failure is a major problem associated with chemoradiation treatment for squamous cell esophageal carcinoma. The aim of this study was to assess the feasibility, efficacy, and toxicity of preoperative radiation (dose > 50 Gy) with platinum‐based chemotherapy followed by esophagectomy in locally advanced squamous cell carcinoma. Methods: Data of patients with cT2‐cT4 or node positive squamous cell carcinoma of the esophagus who received trimodality treatment between February 2006 and June 2015 were reviewed. Results: Forty‐four patients were treated with intensity‐modulated radiation therapy, volumetric‐modulated arc therapy or three‐dimensional radiation therapy. The median radiation dose was 60 Gy. The average volume of the lungs receiving 10 Gy was 48.1%, 20 Gy was 24.5%, and the average mean lung dose was 14 Gy. After chemoradiation, R0 resection was achieved in 31 patients (71%). Patients who received >60 Gy had a higher pathologic complete remission rate than those in the lower dose group (59.1% vs. 36.4%). R0 resection and radiation dose >60 Gy were associated with better overall survival in Cox proportional hazards regression analysis. The median follow‐up duration was 22.4 months and median survival was 25.6 months. Two‐year overall, progression‐free survival and locoregional control rates were 55.9%, 28.6%, and 56%, respectively. The most common grade 3–4 toxicities were esophagitis (63.6%) and neutropenia (25%). Grade 3–4 postoperative morbidities included surgical wound infection (2.3%), acute renal failure (2.3%), and anastomosis stricture (2.3%). Conclusion: Trimodality treatment with a high preoperative radiation dose and chemotherapy yielded a good pathologic complete response rate, and long‐term survival with low toxicities.